PENGARUH MODEL PEMBELAJARAN COOPERATIVE SCRIPT TERHADAP HASIL BELAJAR EKONOMI PESERTA DIDIK - Hidayati, Enik Nur; Suryati, Wawat; Zainal, Vetri Yanti (Jurnal Elastisitas: Kajian Pendidikan Ekonomi, Ilmu Ekonomi, dan Kewirausahaan, 2020)
The problem in this research was the teacher conveyed the learning materials through the talkative method that focused on the teacher and gave the test or task that inclined boring so that impacted to the low of the result of economic learning. This research will apply the learning model of cooperative script that has purpose to know the learning model of cooperative script can increase the result of the students’ economics learning. The method that used in this research was experiment method. The samples that taken in this research was 2 classes, those were Perbankan Syariah class and Akuntansi class. The main technique which was used as the research instrument was 40 questions of multiple choice test. Data analysis technique used Dependent sample of T-test and Independent sample of T-test. After having the hypothesis test on commonality two average test and counting of economics result using statistical formulae, it can be gotten = 3,51 and = 2,00 with the significance 5%. It can be concluded that cooperative script has an influence and can increase the students’ learning result significanly in the Perbankan Syariah class at SMK Negeri 8 Bandar Lampung in 2018/2019